Diversity Of Ephemeroptera, Plecoptera And Trichoptera (Ept) And Its Indication On Stream Quality At Oil Palm Plantation In Bau, Sarawak - Kishen, Bunya (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study was carried out to determine the species diversity of EPT at two rivers in Bau, Sarawak and subsequently assessed the stream quality by using taxa richness of the aquatic insects as the indicators. The two rivers namely Tongga River and Nolan River are located at north-western of the State. Five stations were established in each stream. In oil palm plantation stream, two sites were at downstream, one site within the plantation area and two sites at upstream of the plantation area. In a pristine stream (i.e Tongga River), five stations were studied as the control sites. A two-minute kick-sampling technique was employed in this study and the sampling activities were made between September and October 2008. Environmental variables such as pH, dissolved oxygen, water temperature, nitrate, ammonia, phosphate, total suspended solid, water depth, wetted width and elevation were measured to assess their effects on community structure of EPT. The relationships between the environmental variables and assemblage structure of EPT were analyzed with redundancy analysis. In total, 30 species of EPT were recorded. Community structures of EPT were assessed with ordination technique of redundancy analysis. Analysis showed that EPT were mainly influenced by dissolved oxygen, pH, total suspended solid and depth. Statistically, species diversity between the two rivers was not significant different indicate that effect of oil palm plantation on the overall EPT richness was not present. However, several genera such as Campsoneuria sp., Cinygmula sp., Dolophilodes sp., Ecnomus sp., Epeorus sp., Neoperla sp., Phryganea Sp., Platybaetis sp., Polyplocia sp. 1., Polyplocia sp. 2., Thalerosphyrus sp., Tinodes sp., Thraulus sp. and Tricorythus sp. were sensitive to oil palm plantation thus absent in Nolan River. Biologically, the EPT taxa richness showed that oil palm plantation stream as heavily disturbed while Tongga River as severely disturbed.